Cercetarea calității vieții în România. O analiză a studiilor publicate în revista „Calitatea Vieții” în intervalul 1990−2020 - Țoc, Sebastian (Calitatea Vieții, 2021)
This article proposes a systematic analysis of the main articles relevant to the topic of quality of life published in the Journal Quality of Life, in the period 1990−2020. The aim is to provide a better understanding of the development of this field of research after 1990, in the context of the post-socialist transition, and subsequent integration in the European Union and alignment with European standards. The Quality of Life Journal was one of the most important ways to disseminate the results of the research conducted in Romania; therefore, it can provide a general overview of the social issues addressed in the context of social and economic changes that Romania has gone through in the last 30 years. The conclusions suggest that the period 1990−2000 is one in which the quality of life research is institutionalized, and consolidated after 2000. Since Romania was included in the quality of life European surveys, it was constantly at the end of the EU rankings on most of the quality of life indicators.